Amazonian Chronicles and Indigenous Trading: caths to a documental archaeology of Middle Solimões in the sixteenth and seventeenth centuries - Lopes, Rafael de Almeida (Revista do Museu de Arqueologia e Etnologia, 2021)
The Solimões river was one of the main pathways through where the first european travelers that passed to meet the Amazon for the first time. In the sixteenth and seventeenth centuries, expeditions crossed the river along with chroniclers that described the abundant landscape as well as the diverse and distinct indigenous populations that inhabited its margins. This paper discuss these historical sources regarding the middle course of the Solimões river through the often overlooked perspective of archaeology. To promote this discussion, the mains sources of the time and área will be presented, as well as their production contexts, and the problematics regarding ther analysis. Then, exploratory analysis of the chronicles will be brought forward in relation to descriptions of settlement patterns, practices and products, and exchange networks present in the sources. Lastly, the potential for archaeological and historical research of a documental archaeology in the treatment of these sources will be drafted.